Antibacterial and Antibiofilm Activities of Novel Antimicrobial Peptides against Multidrug-Resistant Enterotoxigenic Escherichia Coli - Wu, Kang-Chi (Int J Mol Sci, 2021)
Post-weaning diarrhea due to enterotoxigenic Escherichia coli (ETEC) is a common disease of piglets and causes great economic loss for the swine industry. Over the past few decades, decreasing effectiveness of conventional antibiotics has caused serious problems because of the growing emergence of multidrug-resistant (MDR) pathogens. Various studies have indicated that antimicrobial peptides (AMPs) have potential to serve as an alternative to antibiotics owing to rapid killing action and highly selective toxicity. Our previous studies have shown that AMP GW-Q4 and its derivatives possess effective antibacterial activities against the Gram-negative bacteria. Hence, in the current study, we evaluated the antibacterial efficacy of GW-Q4 and its derivatives against MDR ETEC and their minimal inhibition concentration (MIC) values were determined to be around 2~32 μg/mL. Among them, AMP Q4-15a-1 with the second lowest MIC (4 μg/mL) and the highest minimal hemolysis concentration (MHC, 256 μg/mL), thus showing the greatest selectivity (MHC/MIC = 64) was selected for further investigations. Moreover, Q4-15a-1 showed dose-dependent bactericidal activity against MDR ETEC in time–kill curve assays. According to the cellular localization and membrane integrity analyses using confocal microscopy, Q4-15a-1 can rapidly interact with the bacterial surface, disrupt the membrane and enter cytosol in less than 30 min. Minimum biofilm eradication concentration (MBEC) of Q4-15a-1 is 4× MIC (16 μg/mL), indicating that Q4-15a-1 is effective against MDR ETEC biofilm. Besides, we established an MDR ETEC infection model with intestinal porcine epithelial cell-1 (IPEC-1). In this infection model, 32 μg/mL Q4-15a-1 can completely inhibit ETEC adhesion onto IPEC-1. Overall, these results suggested that Q4-15a-1 may be a promising antibacterial candidate for treatment of weaned piglets infected by MDR ETEC.